2021
DOI: 10.1590/1984-70332021v21n1n13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of families derived from backcrosses of processed tomato with dwarfism gene

Abstract: In comparison to tomato plants without the dwarfism gene, dwarf tomato plants were shorter, had a smaller canopy diameter and remained upright during maturation, thereby reducing the fruit-soil contact, resulting in healthier fruits. This study evaluated tomato families of a BC 1 F 3 population carrying the dwarf gene for industrial yield. The 150 BC 1 F 3 families and the two parents (hybrid H-9889 and accession BGH-9889) as controls were assessed in an augmented block design with four replications. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…In order to conduct the introgression of genes of interest for different types of biotic stress and fruit nutritional quality, and promote higher productivity, research with dwarf tomato plants has been intensified ( Maciel et al, 2015 , Finzi et al, 2017 , Finzi et al, 2020 , Cavasin et al, 2021 , Gomes et al, 2021 , Oliveira et al, 2022 ). The use of dwarf plants has provided multiple advantages, and obtaining saladette/roma dwarf tomato populations is a promising technology for the future development of higher yielding hybrids, similar to that observed with cherry/grape tomatoes ( Finzi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to conduct the introgression of genes of interest for different types of biotic stress and fruit nutritional quality, and promote higher productivity, research with dwarf tomato plants has been intensified ( Maciel et al, 2015 , Finzi et al, 2017 , Finzi et al, 2020 , Cavasin et al, 2021 , Gomes et al, 2021 , Oliveira et al, 2022 ). The use of dwarf plants has provided multiple advantages, and obtaining saladette/roma dwarf tomato populations is a promising technology for the future development of higher yielding hybrids, similar to that observed with cherry/grape tomatoes ( Finzi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In tomatoes, genes associated with gibberellin and brassinosteroid synthesis and signaling pathways, such as PROCERA, JMJ524, and DWARF, have been identified to regulate plant height (Bassel et al, 2008;Li et al, 2015;Livne et al, 2015;Li et al, 2016). Cavasin et al (2021) evaluated a tomato line carrying the dwarf gene and reported a yield gain of 8.04%. Many dwarf and semi-dwarf cultivars, such as Micro-Tom and Micro-Gold, have been developed as ornamental cultivars or used in genetic transformation studies because of their greater spatial efficiency (Scott et al, 1995;Meissner et al, 1997;Gerszberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%